New Atheism and the Criticism of Islam: From Transnational Discourses to Local Implementation? - Taira, Teemu (Temenos - Nordic Journal for the Study of Religion, 2024)
One of the ideas in the debates concerning anti-Islamic activities is that atheists, especially prominent celebrity atheists – commonly known as ‘New Atheists’ – have provided support and justification for anti-Islamic attitudes and activities. Given that Sam Harris, one of the so-called New Atheists, stated that he started writing his first book, The End of Faith (2004), immediately after the 9/11 attacks, criticism of Islam is expected to be prevalent among some atheists. The more interesting questions, however, concern what kind of criticism there is, how to make sense of its reasons and motivations, whether it dominates the New Atheist agenda (as some argue), and whether the criticism has been somehow influential in various localities. In examining New Atheist publications and their possible presence at the local level, particularly in Finland, this article suggests that an exceptionally pronounced anti-Islamic approach applies mainly to Harris rather than to New Atheism as a whole. Instead, several other significant aspects come into play, highlighted by other New Atheists, and this is largely true of local atheist activism too. Thus, while a weak link between New Atheists and anti-Islamic activities can be made because of their promotion of strong criticism of religion, New Atheism is not the key to understanding such activities, at least in the Finnish context.